Research Progress on the Mechanism of Ferroptosis in Neonatal Hypoxic-ischemic Brain Damage - ZHANG Tianyang, XU Wenxiu, QIN Xinyu, XING Xuexue, BI Meirong (Zhongguo quanke yixue)
Neonatal hypoxic-ischemic brain damage (HIBD) is one of the common causes of neurological injuries in the neonatal period, which is prone to lead to high disability and mortality in newborns, and its pathogenesis is complex and there is no specific treatment in the clinic. Ferroptosis, as a newly discovered type of non-apoptotic cell death in recent years, has received widespread attention and has gradually become a research hotspot. Research on ferroptosis and neonatal HIBD has been increasing year by year, and a large number of studies have shown that ferroptosis is closely related to the occurrence and development of neonatal HIBD. Moreover, it has been pointed out that vitamin K2, especially MK-4, can exert its neuroprotective effect by inhibiting ferroptosis. In this paper, we briefly review the mechanism of ferroptosis in neonatal HIBD and microglia, and look forward to the possibility that vitamin K2, especially MK-4, can improve the prognosis of neonatal HIBD by inhibiting ferroptosis, with the aim of providing a more economical, safer, and more targeted treatment.